Saliva vs. Plasma Bioequivalence of Paracetamol in Humans: Validation of Class I Drugs of the Salivary Excretion Classification System - Idkaidek, N.; Arafat, T. (Drug Research, 2014)
To study saliva and plasma bioequivalence of paracetamol in healthy human volunteers, and to investigate the robustness of using saliva instead of plasma as surrogate for bioequivalence of class I drugs according to the salivary excretion classification system (SECS).Saliva and plasma pharmacokinetic parameters were calculated by non compartmental analysis. Analysis of variance, 90% confidence intervals, intra-subject and inter-subject variability values of pharmacokinetic parameters were calculated after logarithmic transformation. Calculations were done using Kinetica program V5. Descriptive and comparative statistics were also calculated by Excel.Paracetamol falls into class I (High permeability/High fraction unbound to plasma proteins) and was subjected to salivary excretion, with correlation coefficient of 0.99 between saliva and plasma concentrations and saliva/plasma concentrations ratios of 1.45–1.50. The 90% confidence limits of areas under curve (AUClast and AUC∞) showed similar trend and passed the 80–125% acceptance criteria in both saliva and plasma. On the other hand for maximum concentration (Cmax), the 90% confidence limits passed the acceptance criteria in plasma and failed in saliva. Inter and intra subject variability values in saliva were higher than plasma leading to need for higher number of subjects to be used in saliva. Saliva and plasma parameter ratios were not significantly different (P>0.05).Saliva instead of plasma can be used as surrogate for bioequivalence of class I drugs according to SECS when adequate sample size is used. Future work is planned to demonstrate SECS robustness in drugs that fall into classes II or III.
Keywords: salivary excretion classification system; paracetamol; bioequivalence; pharmacokinetics; simCYP